Comment concevoir des référentiels de diplômes professionnels sans renoncer au travail réel ? - Stéphane Balas (Activités)
The object of this text is to show that the design of frames of reference for diplomas, as it is led today, taking little account of the real work, puts the actors concerned into complex situations. The real-life contradictions leave traces in the documents produced. Using frames of reference for diplomas, we attempted to grasp these traces. An alternative proposition makes it possible to produce a result that is useful for future reflection, and to envisage a more coherent design process.